Priming of Anti-tumor Immune Mechanisms by Radiotherapy Is Augmented by Inhibition of Heat Shock Protein 90 - Ernst, Anne; Hennel, Roman; Krombach, Julia; Kapfhammer, Heidi; Brix, Nikko; Zuchtriegel, Gabriele; Uhl, Bernd; Reichel, Christoph A.; Frey, Benjamin; Gaipl, Udo S.; Winssinger, Nicolas; Shirasawa, Senji; et al. (Frontiers in Oncology, 2020)
Radiotherapy is an essential part of multi-modal cancer therapy. Nevertheless, for certain cancer entities such as colorectal cancer the indications of radiotherapy are limited due to anatomical peculiarities and high radiosensitivity of the surrounding normal tissue. The development of molecularly targeted, combined modality approaches may help to overcome these limitations. Preferably, such strategies should not only enhance radiation-induced tumor cell killing and the abrogation of tumor cell clonogenicity, but should also support the stimulation of anti-tumor immune mechanisms – a phenomenon which moved into the center of interest of preclinical and clinical research in radiation oncology within the last decade. The present study focuses on inhibition of heat shock protein 90 (HSP90) whose combination with radiotherapy has previously been reported to exhibit convincing therapeutic synergism in different preclinical cancer models. By employing in vitro and in vivo analyses, we examined if this therapeutic synergism also applies to the priming of anti-tumor immune mechanisms in model systems of colorectal cancer. Our results indicate that the combination of HSP90 inhibitor treatment and ionizing irradiation induced apoptosis in colorectal cells with accelerated transit into secondary necrosis in a hyperactive Kras-dependent manner. During secondary necrosis, dying cancer cells released different classes of damage-associated molecular patterns (DAMPs) that stimulated migration and recruitment of monocytic cells in vitro and in vivo. Additionally, these dying cancer cell-derived DAMPs enforced the differentiation of a monocyte-derived antigen presenting cell phenotype which potently triggered the priming of allogeneic T cell responses in vitro. In summary, HSP90 inhibition – apart from its radiosensitizing potential – obviously enables and supports the initial steps of anti-tumor immune priming upon radiotherapy and thus represents a promising partner for combined modality approaches. The therapeutic performance of such strategies requires further in-depth analyses, especially for but not only limited to colorectal cancer.